THE SEMANTIC FEATURES OF APHORISMS IN ENGLISH AND UZBEK LANGUAGES AND THEIR ROLE IN LINGUO-CULTURE. - Khakimova Mastura Fayzillayevna (Scholar Express Journal, 2025)
This article explores the semantic features of aphorisms in English and Uzbek, examining how these concise expressions of universal truths, wisdom, and life principles reflect the linguistic and cultural aspects of each language. The article discusses the distinctive characteristics of aphorisms in both languages, including their brevity, directness, and cultural relevance. It also highlights their role in shaping social behavior, passing down moral values, and reinforcing cultural identity. The comparison between English and Uzbek aphorisms reveals how language reflects the underlying cultural norms, social structures, and worldviews of each society. This study provides insight into how aphorisms serve as valuable tools for communication, education, and conflict resolution, while also emphasizing the significance of cultural context in shaping expressions of collective wisdom.
Keywords: Aphorisms; Semantics; Linguoculture